2013
DOI: 10.1111/btp.12054
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Regional Vegetation‐climate Dynamics for Middle America: Tropical Versus Temperate Applications

Abstract: Regional vegetation‐climate modelling studies have typically focused on boreal or temperate ecosystems in North America and Europe, almost completely overlooking tropical ecosystems. We present the first results of simulated regional vegetation‐climate dynamics in Middle America as simulated by the model, LPJ‐GUESS. The Kappa statistic indicated poor agreement, with a Kappa value of 0.301. When we modified the Kappa statistic by aggregating cell sizes and using generalized biomes, the Kappa value increased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…To this end, we first classified each stand into one of eight major biomes. The classification mainly followed the biomization scheme by Snell et al 16 . An exception were the tropical needle-leaved forests (TrNE), which are not parameterized as a seperate PFT in LPJ-GUESS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we first classified each stand into one of eight major biomes. The classification mainly followed the biomization scheme by Snell et al 16 . An exception were the tropical needle-leaved forests (TrNE), which are not parameterized as a seperate PFT in LPJ-GUESS.…”
Section: Methodsmentioning
confidence: 99%
“…An exception were the tropical needle-leaved forests (TrNE), which are not parameterized as a seperate PFT in LPJ-GUESS. While in trial runs we tested implementing an additional TrNE class similar to Snell et al 16 , this new PFT showed very little growth, probably due to strong competition with the temperate broadleaved evergreen (TeBE) and C4 grass PFTs. Within the natural forests of Central America the predominant conifers are pines, which co-occur with temperate broadleaves (mostly oaks) and inhabit areas with seasonal drought 81 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most global scale DGVMs are generic and have simple representation of various vegetation types for example tropical areas are typically represented by few PFTs (Snell, Cowling and Smith, 2013). They are optimized to reproduce overall patterns, temporal variability and carbon stocks of vegetation and soil at global scale, but do often not provide reliable estimates at regional scales (Tang et al, 2010).…”
Section: Current Status Of Vegetation Modelling In South Asiamentioning
confidence: 99%
“…While some global-scale studies have investigated the potential effect of Chapter 3-Climate change and elevated CO2 favor forest over savanna under different future scenarios in South Asia increasing CO2 on natural vegetation, carbon sequestration and biome boundaries (e.g. Hickler et al, 2006;Sato et al, 2007;Smith et al, 2013), detailed modelling studies focusing explicitly on different biomes in South Asia have not been conducted. The physiological effects of increased CO2 and climate change on South Asian vegetation is uncertain and needs to be addressed in order to improve understanding of regional ecosystem functioning as well as implications for biodiversity conservation.…”
Section: Introductionmentioning
confidence: 99%